IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) SEBAGAI PENDUKUNG KEPUTUSAN PEMBELIAN SEPEDA MOTOR (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
Motorbikes as a means of transportation with a high level of interest have been considered as one of the needs. Motorbikes are in great demand by the community because they are easier to use, more practical when in traffic and so on. The more motorcycle enthusiasts, the more motorcycle manufacturers. Motorcycle consumers find it difficult to make the right choice when choosing a motorcycle. The purpose of this study is to provide consumers with a choice of motorbikes that are in accordance with predetermined criteria. Creating a system that can be used to help the decision-making process in purchasing a motorcycle. The method used in solving this problem uses Simple Additive Weighting.
Keywords: Simple Additive Weighting; Motorcycle; Decision Support System